Phytoplankton community structure at the juncture of the Agulhas Return Front and Subtropical Front in the Indian Ocean sector of Southern Ocean: Bottom-up and top-down control. (August 2015) - Naik, Ravidas Krishna; George, Jenson V.; Soares, Melena A.; Devi, Asha; N, Anilkumar; Roy, Rajdeep; Bhaskar, P.V.; Murukesh, Nuncio; Achuthankutty, C.T.
Abstract: The juncture of the Agulhas Return Front (ARF) and Subtropical Front (STF) in the Indian Ocean sector of Southern Ocean (SO) is characterized by high mesoscale turbulence, which results in sporadic, short lived phytoplankton proliferation. The biota, mainly the phytoplankton community from such a complex hydrodynamic region and its response to the mesoscale turbulence, are areas of interest for investigation. Hence, during the sixth Indian expedition to SO, a two-day time series was occupied at the ARF and STF merged region (40°S 58°30′E) from 13 to 15 January, 2012. The vertical profiles of phytoplankton (based on pigment indices) indicated variation in the percentage contribution of phytoplankton functional groups (Micro, Nano and Pico). Though the overall community structure was dominated by nanoplankton, as exhibited by pigment indices and CHEMTAX analysis, drastic shifts in the community were observed at 120 m depth at six hourly intervals. The oscillation between Flagellates (nanoplankton) to prokaryotes (picoplankton) and then to diatoms (microplankton) at this depth in three consecutive observations coincided with the significant variations in phosphate and nitrate concentrations, along with increase in abundance of the grazer community (ciliates and heterotrophic dinoflagellates). From the present study, it is evident that the flagellate group is the ideal one to survive in such a complex regime. However, the observed small interval oscillation in the phytoplankton community could be a coupled effect of bottom-up (vertical advection that alters the nutrient flux), and top-down (increased abundance of microzooplankton) factors.